2020
DOI: 10.3390/app10207247
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Site-Specific Design Spectrum on Earthquake-Building Parameters: A Case Study from the Marmara Region (NW Turkey)

Abstract: The Marmara Region (NW Turkey) has experienced significant earthquakes (M > 7.0) to date. A destructive earthquake is also expected in the region. To determine the effect of the specific design spectrum, eleven provinces located in the region were chosen according to the Turkey Earthquake Building Code updated in 2019. Additionally, the differences between the previous and updated regulations of the country were investigated. Peak Ground Acceleration (PGA) and Peak Ground Velocity (PGV) were obtained for ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(18 citation statements)
references
References 65 publications
0
16
0
2
Order By: Relevance
“…The U.S. Geological Survey ShakeMap recorded a ground motion intensity of VIII, with the epicenter being 19 Km to the South-East of Kodari. It has been investigated that the site-specific design spectrum and ground motion intensity have a significant effect on the performance of the building's parameters against earthquakes [51].…”
Section: Background Of the Selected Earthquakesmentioning
confidence: 99%
“…The U.S. Geological Survey ShakeMap recorded a ground motion intensity of VIII, with the epicenter being 19 Km to the South-East of Kodari. It has been investigated that the site-specific design spectrum and ground motion intensity have a significant effect on the performance of the building's parameters against earthquakes [51].…”
Section: Background Of the Selected Earthquakesmentioning
confidence: 99%
“…Seismogenic zone 6 covers the NW-SE striking Erzincan basin which appears to be a major step over along the NAFZ (Şengör, 1979;Hubert-Ferrari et al, 2002). The largest events in this seismogenic Okay and Tüysüz, 1999;Yiğitbaş et al, 2004;USGS, 2010;Ekinci et al, 2020Ekinci et al, , 2021Işık et al, 2020 We used instrumental (M S ≥ 5.5, until the end of 2019) and historical data with maximum intensities of I 0 ≥ 9.0 corresponding to surface wave magnitude M S ≥ 7.0 (Sayıl, 2013). Different-scaled magnitudes were transformed to M S using empirical equations obtained from regional earthquakes (Figure 3).…”
Section: Rtimap Modelmentioning
confidence: 99%
“…Figure 1. Tectonic map of Turkey and the surrounding (compiled withOkay and Tüysüz, 1999;Yiğitbaş et al, 2004; USGS, 2010;Ekinci et al, 2020Ekinci et al, , 2021Işık et al, 2020). NAFZ, North Anatolian Fault Zone; EAFZ, East Anatolian Fault Zone; NEAFZ, Northeast Anatolian Fault Zone; BZSZ, Bitlis-Zagros Suture Zone; DSFZ, Dead Sea Fault Zone; WAGS, West Anatolian Graben System; SBST, Southern Black Sea Thrust.…”
mentioning
confidence: 99%
“…It is very important to extend the time in the first two limits. In Reference [ 7 ], the authors also mentioned the possible positive effect of non-structural elements on the behavior of structures during an earthquake. Some of the authors [ 8 , 9 ] indicated the impact of irregularities on the structure of its seismic characteristics.…”
Section: Introductionmentioning
confidence: 99%